How are words felt in a second language: Norms for 2, 628 English words for valence and arousal by L2 speakers. Issue 2 (26th March 2021) - Imbault, Constance; Titone, Debra; Warriner, Amy Beth; Kuperman, Victor
Abstract: The topic of non-native language processing has been of steady interest in past decades. Yet, conclusions about the emotional responses in L2 have been highly variable. We conducted a large-scale rating study to explicitly measure how non-native readers of English respond to the valence and arousal of 2, 628 English words. We investigated how the effect of a rater's L2 proficiency, length of time in Canada, and the semantic category of the word affects how L2 readers experience and rate that word. L2 speakers who had lived a longer time in Canada, and reported higher English proficiency, showed emotional responses that were more similar to those of L1 speakers of English. Additionally, valence differences between L1 and L2 raters were greater in words that L2 raters do not typically use in English. These findings highlight the importance of behavioural ecology in language learning, particularly as it applies to emotional word processing.